CRISPR/Cas9 mediated ENT2 gene knockout altered purine catabolic pathway and induced apoptosis in colorectal cell lines. - Safaa M Naes; Sharaniza Ab-Rahim; Musalmah Mazlan; Saiful Effendi Syafruddin; M Aiman Mohtar; Asmaa Y Abuhamad; Amirah Abdul Rahman (PLoS ONE)
Although purine metabolism is one of the most impacted pathways in colorectal cancer (CRC), little is known about the role of equilibrative nucleoside transporter 2 (ENT2) in CRC development and its association with the altered purine metabolism pathway. This study aimed to determine the role of ENT2 in altered purine metabolism in the early and late stages of CRC using CRISPR/Cas9 gene editing tools and a variety of functional experiments. The expression of ENT2 was significantly higher (P < 0.001) in all CRC cell lines as compared to the normal colon cells. The two CRC cell lines with the highest ENT2 expression, the early stage HT29 cells and the late stage DLD1 cells, were knocked out (KO) using the CRISPR/Cas9 tool. The hypoxanthine (HPX) level and the xanthine oxidase (XO) activity were significantly higher in both HT29/KO and DLD1/KO single cell-derived clones (P < 0.01). The increase in HPX level and XO activity were associated with an elevation in the reactive oxygen species (ROS) level. These data suggest that the ENT2 KO elevated the ROS levels induced apoptosis and impaired the cell proliferation of the early stage of CRC cell line, i.e., HT29/KO clonal cells. In this context, targeting ENT2 gene might be a potential strategy in CRC treatment by increasing the production of ROS and hence, inducing the apoptosis pathway.